Aging and Degradation of Optical Fiber Parameters in a 16-Year-Long Period of Usage. Issue 1 (2nd January 2020) - Maslo, Anis; Hodzic, Mujo; Skaljo, Edvin; Mujcic, Aljo
ABSTRACT: The first generation of installed optical cables in Eastern Europe has been in use for more than 20 years. This paper analyzes the change of optical fibers from the aspect of aging under the influence of transmitted signals and the aspect of parameter degradation during exploration. The paper provides the answer for how to repair the increased attenuation at 1310 nm. We also proposed the method of solution NG PON access for small remote villages that are situated along the analyzed route.